Ocena skuteczności wybranych metod fizjoterapii w zmianach zwyrodnieniowych odcinka lędźwiowego kręgosłupa = Evaluation of the effectiveness of selected methods of physiotherapy in degenerative changes of lumbar spine - Zawadka, Magdalena; Fijewski, Adam; Gawda, Piotr (Journal of Education, Health and Sport, 2015)
Zawadka Magdalena, Fijewski Adam, Gawda Piotr. Ocena skuteczności wybranych metod fizjoterapii w zmianach zwyrodnieniowych odcinka lędźwiowego kręgosłupa = Evaluation of the effectiveness of selected methods of physiotherapy in degenerative changes of lumbar spine. Journal of Education, Health and Sport. 2015;5(11):373-388. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34100 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A373-388 https://pbn.nauka.gov.pl/works/671008 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.09.2015. Revised 25.10.2015. Accepted: 20.11.2015. Ocena skuteczności wybranych metod fizjoterapii w zmianach zwyrodnieniowych odcinka lędźwiowego kręgosłupa Evaluation of the effectiveness of selected methods of physiotherapy in degenerative changes of lumbar spine Magdalena Zawadka, Adam Fijewski1, Piotr Gawda2 1Studium Wychowania Fizycznego i Sportu Uniwersytetu Medycznego wLublinie (Department of Physical Education and Sport, Medical University of Lublin) 2Zakład Rehabilitacji i Fizjoterapii Uniwersytetu Medycznego w Lublinie (Department of Rehabilitation and Physiotherapy, Chair of Rehabilitation, Physiotherapy and Balneotherapy, Faculty of Health Sciences, Medical University of Lublin) Corresponding author: mgr Magdalena Zawadka Medical University of Lublin 05-334 Latowicz Transbór 9 magdalenazawadka91@gmail.com Streszczenie Wstęp Zwyrodnienia odcinka lędźwiowego kręgosłupa stanowią częstą przyczynę korzystania z fizjoterapii. Celem pracy była ocena skuteczności podejmowanych metod usprawniania u pacjentów ze zmianami zwyrodnieniowymi. Materiał i metoda Badania przeprowadzono w dwóch grupach pacjentów. W pierwszej grupie zastosowano fizykoterapię i mobilizacje a w drugiej fizykoterapie, mobilizacje i ćwiczenia w wodzie. Do oceny skuteczności postępowania użyto kwestionariusza Oswestry, skali VAS, autorskiej ankiety oraz testów funkcjonalnych. Wyniki Odnotowano zmniejszenie dolegliwości bólowych w obu grupach usprawniania (p< 0,001). Zmniejszenie wskaźnika niesprawności wynosiło w obu grupach około 10 punktów procentowych. Poprawie uległa ruchomość odcinka lędźwiowego średnio o 1,8 cm w grupie I i 1,6cm w grupie II. Zmniejszyła się liczba osób z objawami neurologicznymi w obu grupach. Nie odnotowano znaczących różnic w wynikach miedzy grupami poza bardziej przeciwbólowym efektem terapii w grupie I (p=0,032). Wnioski Metody fizjoterapii charakteryzują się porównywalną skutecznością w usprawnianiu pacjentów ze zmianami zwyrodnieniowymi odcinka lędźwiowego kręgosłupa. Zaburzenia sprawności oraz dolegliwości bólowe ulegają zmniejszeniu w wyniku zastosowanych zabiegów fizjoterapeutycznych. Wyniki wybranych testów funkcjonalnych nie zależały od rodzaju podjętego postępowania fizjoterapeutycznego. Słowa kluczowe: fizjoterapia, zmiany zwyrodnieniowe, odcinek lędźwiowy kręgosłupa. Abstract Introduction Lumbar spine degeneration is often cause of using the physiotherapy. The aim of this study was to evaluate the effectiveness of rehabilitation methods in patients with osteoarthritis. Material and methods The study was investigate in two groups of patients. In the first group was used physical therapy methods and mobilizations, in the second physical therapy, mobilizations and exercises in water. To evaluate the effectiveness of the procedure were used the Oswestry questionnaire, visual-analog scale, the author’s questionnaire and functional tests. Results There has been a reduction of pain in both groups of improvement (p <0.001). Reducing the rate of disability in both groups was about 10 percentage points. Has improved the mobility of the lumbar spine by an average of 1.8 cm in group I and 1.6 cm in group II. Decline in the number of people with neurological symptoms in both groups. There were no significant differences in outcome between the groups except more analgesic therapy effect in group I (p = 0.032). Conclusions Physiotherapy methods are characterized by comparable effectiveness in improving patients with osteoarthritis of the lumbar spine. Disability efficiency and pain are reduced as a result of the applied physical therapy. The results of selected functional tests did not depend on the type of undertaken physiotherapy proceedings. Keywords: physiotherapy, osteoarthritis, lumbar spine.